Pengaruh aplikasi health promotion model terhadap peningkatan kualitas kelompok peduli hipertensi - Triyanto, Endang; Iskandar, Asep; Saryono, (Jurusan Keperawatan FIKES UNSOED, 2012)
Uncontrolled hypertension can lead to heart disease. Hypertension Care Group (HCG) was formed with the concept of, by and for people with hypertension. Improving the quality of HCG implemented a series of training cadres which is an application of health promotion models. This research was a quasi-experimental pre post test without control group design to member of HCG in Pamijen, Sokaraja. Technique of sampling are total sampling were 30 respondents. Results found chi squere test, p value = 0.001, which means there is a significant increase in the quality of HCG after getting treatment applications health promotion model. Form of treatment in the form of training consisting management training music therapy, hypertension, nursing therapy. Guidance from health centers and district health offices should be improved so that all activities can be run in sustainability